Association between maternal depressive symptoms in the early post‐natal period and responsiveness in feeding at child age 2 years. Issue 4 (1st May 2014) - Mallan, Kimberley M.; Daniels, Lynne A.; Wilson, Jacinda L.; Jansen, Elena; Nicholson, Jan M.
Abstract Maternal depression is a known risk factor for poor outcomes for children. Pathways to these poor outcomes relate to reduced maternal responsiveness or sensitivity to the child. Impaired responsiveness potentially impacts the feeding relationship and thus may be a risk factor for inappropriate feeding practices. The aim of this study was to examine the longitudinal relationships between self‐reported maternal post‐natal depressive symptoms at child age 4 months and feeding practices at child age 2 years in a community sample. Participants were Australian first‐time mothers allocated to the control group of the NOURISH randomized controlled trial when infants were 4 months old. Complete data from 211 mothers (of 346 allocated) followed up when their children were 2 years of age (51% girls) were available for analysis. The relationship between Edinburgh Postnatal Depression Scale (EPDS) score (child age 4 months) and child feeding practices (child age 2 years) was tested using hierarchical linear regression analysis adjusted for maternal and child characteristics. Higher EPDS score was associated with less responsive feeding practices at child age 2 years: greater pressure [β = 0.18, 95% confidence interval (CI): 0.04–0.32, P = 0.01], restriction (β = 0.14, 95% CI: 0.001–0.28, P = 0.05), instrumental (β = 0.14, 95% CI: 0.005–0.27, P = 0.04) and emotional (β = 0.15, 95% CI: 0.01–0.29, P = 0.03) feeding practices (ΔR2 values: 0.02–0.03, P < 0.05). This study provides evidence for the proposed link between maternal post‐natal depressive symptoms and lower responsiveness in child feeding. These findings suggest that the provision of support to mothers experiencing some levels of depressive symptomatology in the early post‐natal period may improve responsiveness in the child feeding relationship.